Organizational forms and knowledge absorption - Radovanović, Nikola; Matović, Danijela S (Industrija, 2016)
Managing the entire portion of knowledge in an organization is a challenging task. At the organizational level, there can be enormous quantities of unknown, poorly valued or inefficiently applied knowledge. This is normally followed with the underdeveloped potential or inability of organizations to absorb knowledge from external sources. Facilitation of the efficient internal flow of knowledge within the established communication network may positively affect organizational capacity to absorb or identify, share and subsequently apply knowledge to commercial ends. Based on the evidences that the adoption of different organizational forms affects knowledge flows within an organization, this research analyzed the relationship between common organizational forms and absorptive capacity of organizations. In this paper, we test the hypothesis stating that the organizational structure affects knowledge absorption and exploitation in the organization. The methodology included quantitative and qualitative research method based on a questionnaire, while the data has been statistically analyzed and the hypothesis has been tested with the use of crosstabulation and chi-square tests. The findings suggest that the type of organizational form affects knowledge absorption capacity and that having a less formalized and more flexible structure in an organization increases absorbing and exploiting opportunities of potentially valuable knowledge.
Keywords: Communication network; Absorptive capacity; Organizational form; Knowledge